Radiation-induced formation of purine lesions in single and double stranded DNA: revised quantification - Terzidis, Michael A.; Ferreri, Carla; Chatgilialoglu, Chryssostomos (Frontiers in Chemistry, 2015)
The formation of oxidative lesions arising from double stranded DNA damage is of major significance to chemical biology from the perspective of application to human health. The quantification of purine lesions arising from γ-radiation-induced hydroxyl radicals (HO•) has been the subject of numerous studies, with discrepancies on the measured 5′,8-cyclo-2′-deoxyadenosine (cdA) and 5′,8-cyclo-2′-deoxyguanosine (cdG) lesions reported by different groups. Here we applied an ameliorative protocol for the analysis of DNA damage with quantitative determination of these lesions via isotope dilution liquid chromatography coupled with tandem mass spectrometry. Tandem-type purine lesions were quantified along with 7,8-dihydro-8-oxo-2′-deoxyguanosine (8-oxo-dG) and 7,8-dihydro-8-oxo-2′-deoxyadenosine (8-oxo-dA) in single and double stranded DNA, generated during DNA exposure to diffusible HO• radicals in the absence or presence of physiological levels of oxygen. The cdA and cdG lesions in absence of oxygen were found ~2 times higher in single than double stranded DNA, with 5′R being ~6.5 and ~1.5 times more predominant than 5′S in cdG and cdA, respectively. Interestingly, in the presence of 5% molecular oxygen the R/S ratios are retained with substantially decreased yields for cdA and cdG, whereas 8-oxo-dA and 8-oxo-dG remain nearly constant. The overall lesion formation follows the order: 8-oxo-dG >> 8-oxo-dA > 5′R-cdG > 5′R-cdA > 5′S-cdA > 5′S-cdG. By this method, there was a conclusive evaluation of radiation-induced DNA purine lesions.